Urgensi Pendidikan Bela Negara Dalam Membentuk Kecerdasan Sosial Peserta Didik Sebagai Daya Dukung Pertahanan Negara - Imran Hasyim; Anang P Utama; Bayu Setiawan (UIN Fatmawati Sukarno Bengkulu, 2022)
Every citizen has the right and obligation to participate in national defense efforts. The application of the five basic values of defending the country as an important element in the Fostering of Awareness of State Defense is a measure of the achievement of state defense education. The development of the dynamics of problems in the world of education such as bullying, brawls, and drugs as one of the threats to national defense. So that this study aims at explaining that state defense education can be one of the factors forming social intelligence for students, a strategy in optimizing state defense education. The qualitative approach in this research is to describe data collection through literature study. The overview shows that the understanding of students' attitudes and behavior towards state defense education and understanding of the urgency of state defense education as an effort to defend the country. The conclusion is that the state defense education curriculum that is included in the relevant subjects has five basic values, namely love for the homeland, self-sacrifice, awareness of the nation and state, Pancasila as the state ideology, and the ability to defend the country both physically and non-physically. A good educational process will produce students with character in maximizing the intelligence potential of each student.